2018
DOI: 10.1186/s10194-018-0923-6
|View full text |Cite
|
Sign up to set email alerts
|

Early onset of efficacy with erenumab in patients with episodic and chronic migraine

Abstract: BackgroundSubcutaneous erenumab reduced monthly migraine days and increased the likelihood of achieving a ≥ 50% reduction at all monthly assessment points tested in 2 pivotal trials in episodic migraine (EM) and chronic migraine (CM). Early efficacy of migraine preventive medications is an important treatment characteristic to patients. Delays in achievement of efficacy can result in failed adherence. The objective of these post-hoc analyses were to evaluate efficacy in the first 4 weeks after initial subcutan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
59
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 87 publications
(73 citation statements)
references
References 19 publications
13
59
0
1
Order By: Relevance
“…Finally, the eligible studies were checked for data sources and they were found to be from 16 RCTs. These trials were included in this study for qualitative and quantitative synthesis [39,40,41,42,43,44,45,46,47,48,49,50,52,53,54,55,56,57,58,59,60,61,62,63,64]. The flow diagram of evidence selection is presented in Figure 1.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, the eligible studies were checked for data sources and they were found to be from 16 RCTs. These trials were included in this study for qualitative and quantitative synthesis [39,40,41,42,43,44,45,46,47,48,49,50,52,53,54,55,56,57,58,59,60,61,62,63,64]. The flow diagram of evidence selection is presented in Figure 1.…”
Section: Resultsmentioning
confidence: 99%
“…Secondary endpoints included the usage times of migraine-specific medication, cumulative hours of headache, Headache Impact Test 6 (HIT-6) score, and Migraine Specific Quality of Life Questionnaire (MSQ) score. All the trials indicated better outcomes and prevention of migraine with anti-CGRP medication, but the efficacy seemed to be diversified by the different interval and period of drug administration [39,40,41,42,43,44,45,46,47,48,49,50,51,52,53,54,55,56,57,58,59,60,61,62,63,64]. Though the synthesized evidences consistently confirmed that anti-CGRP had no serious adverse events reported and the effects of anti-CGRP remain controversial due to differences in follow-up and the percentage of response rate [65,66,67,68,69].…”
Section: Introductionmentioning
confidence: 99%
“…Consistent with findings from previous global studies of episodic and chronic migraine, 19 responses to erenumab in the Japan study were The analysis included randomized patients who received ≥1 dose of investigational product and had ≥1 postbaseline measurement during the double-blind treatment phase. Consistent with findings from previous global studies of episodic and chronic migraine, 19 responses to erenumab in the Japan study were The analysis included randomized patients who received ≥1 dose of investigational product and had ≥1 postbaseline measurement during the double-blind treatment phase.…”
Section: Discussionmentioning
confidence: 97%
“…In this population of Japanese patients with episodic migraine, preventive treatment with erenumab 70 and 140 mg led to statistically significant improvements in each of the efficacy endpoints -change from baseline in MMD and MSMD as well as achievement of ≥50% response. Consistent with findings from previous global studies of episodic and chronic migraine, 19 responses to erenumab in the Japan study were The analysis included randomized patients who received ≥1 dose of investigational product and had ≥1 postbaseline measurement during the double-blind treatment phase. The adjusted analysis utilized a generalized linear mixed model, which included treatment, visit, treatment by visit interaction, stratification factor (previous/current treatment with migraine-preventive medication), and baseline value as covariates and assumed a first-order autoregressive covariance structure.…”
Section: Discussionmentioning
confidence: 97%
“…22 A pooled analysis of these trials suggested that the benefit of erenumab was evident within the first week of treatment in chronic and episodic migraine. 23 These findings are supported by the ARISE study, which showed that erenumab 70mg weekly reduced monthly migraine days by 2.9 compared with 1.8 with placebo after 12 weeks' treatment (p<0.001). 24 Of patients treated with erenumab, 40% experienced a ≥50% reduction in migraine frequency (versus 30% with placebo, p=0.010).…”
Section: Erenumabmentioning
confidence: 64%